Uncomplicated urinary tract infection in pregnant women. Modern views on treatment and prevention - O. B. Poselyugina (Лечащий Врач)
In the article, modern views on urinary tract infection in pregnant women are presented. The features of antibacterial therapy depending on the localization of the infectious process in the urinary tract are revealed, the tactics of management of pregnant women according to clinical recommendations are given. Phytotherapy and prevention in this disease are covered.